EFFECT OF NATURAL FEED MULBERRY AND GLIRICIDIA AGAINST PERCENTAGE NON CARCASS AND CARCASSES MALES GOAT ETTAWA CROSSBREED - Suparman Suparman; Harapin Hafid; La Ode Baa (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aims to assess the effect of natural feed mulberry and glicidia against carcass percentage and non-carcass male goats Ettawa crossbreed. This study was conducted for 4 months starting in January to April 2016, located in the Village RanomentaaToari District of Kolaka. This study used 12 male goats Crossbreed Ettawa age ranges of 4-6 months that were placed in 12 individual cages. The materials used are natural feed (Gliricidia leaves and mulberry leaves), water, salt, and medicine. The equipment used is the individual cages, where food, drinking, machetes, scales, basins, cutter, knife, plastic bags, rope and a cutting table. The design used in this study is completely randomized design (CRD) 3 treatments with 4 replications. Treatment 1 (T1) (100% mulberry leaf), T2 (50% of mulberry leaves, 50% Gliricidia leaves) and T3 (100% Gliricidia leaves). The parameters were observed in the study were: weight gain (WG), slaughter weight, carcass weight and percentage, and the percentage of non-carcass weight. The results showed that the average W. Gited Nations T3 (26.98 g/day) was significantly different (P0.05) with T2 (22.83 g/day) and T1 (22.42 g/day), but T2 and T1 are not significantly different. In line with the average slaughter weight is from highest to lowest T3 (13.29 kg), T2 (11.21 Kg) and T1 (10.37 Kg). Followed by the average carcass weight were significant (P0.05) as a result of treatment. The average carcass weight T1 (4.17 Kg), T2 (4.24 Kg) and T3 ((5.38 kg). Whereas in the average carcass percentage effect is not significant (P0.05) as a result of treatment with a range of 38.43 -39.43%. Similarly, the weight of non Kakas and non carcass percentage of the average range of 50.73 to 55.09%. Based on the results research, it can be concluded that the natural feeding mulberry and gliricidia real effect on body weight gain, slaughter weight and carcass weight but had no effect on carcass percentage, non carcass weight and carcass percentage